A Bio-Guided Fractionation to Assess the Inhibitory Activity of Calendula officinalis L. on the NF-κB Driven Transcription in Human Gastric Epithelial Cells. (28th September 2015) - Colombo, Elisa; Sangiovanni, Enrico; D'Ambrosio, Michele; Bosisio, Enrica; Ciocarlan, Alexandru; Fumagalli, Marco; Guerriero, Antonio; Harghel, Petru; Dell'Agli, Mario
Abstract : Calendula officinalis L. has been largely known for its topical anti-inflammatory properties; however, there are no experimental evidences about its antiphlogistic effect at the gastric level. To investigate whether marigold might exert an activity against gastric inflammation, a CH2 Cl2 extract obtained from C. officinalis flowers was evaluated in vitro on the NF- κ B pathway. The lipophilic extract demonstrated a significant inhibitory effect on the NF- κ B driven transcription. The identification of active compounds was conducted by a bio-guided fractionation of the extract that afforded 16 fractions. Fraction J exhibited a concentration-dependent inhibitory activity on the NF- κ B driven transcription and significantly contributed to the antiphlogistic effect showed by CH2 Cl2 extract. The main components of fraction J were loliolide and the fucoside acetates of β -eudesmol and viridiflorol. HPLC analysis of fractions D and E led to the identification and isolation of triterpene esters that showed a concentration-dependent inhibition of the NF- κ B driven transcription, with faradiol-3-myristate and the corresponding aglycone being the most active compounds. The present study provides some experimental evidences that Calendula officinalis L. may exert an anti-inflammatory activity on the gastric district by the inhibition of the NF- κ B system, identifying the compounds responsible, at least in part, for the observed effect.